2020
DOI: 10.11591/ijere.v9i1.20365
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong learning tendencies of trainers in adult education

Abstract: <span>Life-long learning competencies, skills and attitudes are of having significance for education processes. The study was designed based on the correlational survey model. Population consists of 354 trainers in Public Education Centers in Samsun. In terms gender, there was a significant difference in lack of regulation and lack of curiosity dimension in favour of females in terms of lifelong learning tendencies. It was found that as the age level increases, the tendency to persistence which is the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The remaining components were scored moderately. Although that is not a bad result, it is worth paying attention to the data in the sense that a lack of skills in goal-setting or in self-direction might lead to a drop in motivation to learn, particularly in the adult population (Sentürk & Duran, 2020). Similarly, not participating in the process of self-evaluation, including in formal environments, may prevent the development of optimum skills for LLL (Deveci, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining components were scored moderately. Although that is not a bad result, it is worth paying attention to the data in the sense that a lack of skills in goal-setting or in self-direction might lead to a drop in motivation to learn, particularly in the adult population (Sentürk & Duran, 2020). Similarly, not participating in the process of self-evaluation, including in formal environments, may prevent the development of optimum skills for LLL (Deveci, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lifelong learning is characterized by being a conscious, person-centered action, the social and collaborative nature of which is particularly important (Grokholskyi et al, 2020). In this regard, the PLE approach may be complementary in successfully achieving the skills and carrying out the main activities of LLL, which are extremely important for formal and informal educational processes (Sentürk & Duran, 2020). Using the characteristics of LLL and PLE as a reference, we carried out a study to identify and evaluate the connections between the two concepts, and the implications of that on students' higher education.…”
Section: Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of past research shows that females possess higher LLL tendencies than their male counterparts. Furthermore, Şentürk and Duran [25] reported that there was a significant difference in the lack of regulation and lack of curiosity dimension in favor of females in terms of LLL tendencies. In contrast, Yüzbaşioğlu et al [26] concluded that female undergraduates had a higher score average than males for motivation, persistence, lack of curiosity and general LLL tendency scores.…”
Section: Lifelong Learning Tendenciesmentioning
confidence: 98%
“…Regarding older adults in the first training program, entitled 'Nutrition for Older Adults' and the second training program, entitled 'Recreation for Older Adults' the results indicated that older adults' satisfaction with the overall training programs in terms of knowledge and skills gained as well as trainers and activities were at the highest level (100%). Age level increases, the tendency to persistence which is the sub-factor of lifelong tendencies increases [33].…”
Section: Student Satisfaction With Regard To Collaborative Project-ba...mentioning
confidence: 99%